A New Reference Axis for Tibial Component Rotation in Total Knee Arthroplasty: A Three-dimensional Computed Tomography Analysis - Jin, Yan; Li, Pingyue; Yang, Yiming; Zeng, Xianli; Shen, Hongyuan; Zhang, Lihang; Tsai, Tsung-Yuan; Chen, Jiarong (Frontiers in Surgery, 2022)
To introduce a new reference axis of tibial rotation in total knee arthroplasty (TKA) and verify the reliability.A consecutive series of 80 knees that underwent TKA from 2018 to 2020 and 80 healthy knees were analyzed using a three-dimensional tibial model. A coordinate system was established based on standard TKA tibial cutting. The line connecting the lateral-tibial eminence and medial 1/3 of the tibial tubercle or the medial border of the tibial tubercle was identified as the lateral-eminence line (LE line) and the medial lateral-eminence line (MLE line), respectively. In order to evaluate the reliability of the new reference axis, Akagi’s line, the medial third of the tibial tubercle (1/3 line) were used to compare with LE line and MLE line by measuring the angle between the lines and Z-axis. Under the coronal view, the intersection angle (TPA) which between the line connecting the center of medial and lateral tibial plateau with the Z-axis was measured.The mean angle between Akagi’s line and Z-axis in the healthy group and the osteoarthritis (OA) group was 87.57°±3.48°and 87.61°±3.47°, respectively. The mean angle between the LE line and Z-axis in the healthy group and the OA group was 87.15°± 4.13°and 86.78°± 3.95°, respectively. A weak correlation was found between the TPA and Akagi’s line and the 1/3 line. A moderate correlation was found between the TPA and LE lines. There were no significant differences between the healthy group and OA group (P>0.05) in all four reference axes. The LE line that showed excellent intra-/inter-observer reliability and reproducibility. The novel and easily drawn LE line can be a preferable option using for tibial component rotational alignment in TKA.